Representation of social conflict in Poppi Pertiwi's novel Septihan - Nur Alyani; Masduki Zakaria; Nina Queena Hadi Putri; Alfian Rokhmansyah; Nia Novita Putri (Pioneer: Journal of Language and Literature, 2026)
This study aims to analyze the representation of social conflict in Poppi Pertiwi’s novel Septihan using Ian Watt’s sociological approach to literature. This study employs a qualitative descriptive method, utilizing data in the form of dialogue and narrative excerpts that represent social conflict within the novel. Data collection was conducted through literature review using the read-and-note technique. Data analysis focused on three concepts of Ian Watt’s literary sociology: the author’s social context, literature as a reflection of societal life, and the social function of literature. The research findings reveal family conflicts reflected in Septian’s strained relationship with his parents, stemming from family pressure and a lack of attention. Interpersonal conflicts are evident in Septian’s relationships with his school friends, particularly those influenced by misunderstandings, bullying, and adolescent social competition. Meanwhile, the different treatment received by some characters due to their economic backgrounds and popularity within the school environment highlights the social status conflict. These findings suggest that this novel not only depicts adolescent social dynamics but also contains social criticism of patterns of family relationships, social circles, and social inequality in society.